Insight in the Prediction of Chemotherapy-Induced Nausea - Roscoe, Joseph A. (2009)
PURPOSE: To identify risk factors for chemotherapy-related nausea. METHODS: We examined risk factors for nausea in 1696 patients from three multicenter studies conducted from 1998 to 2004. All patients were beginning a chemotherapy regimen containing cisplatin, carboplatin, or doxorubicin. Nausea was assessed on a 1 – 7 scale four times a day for four days by diary RESULTS: 1) Average nausea for breast cancer patients receiving doxorubicin (mean = 2.31) was significantly greater than for other patients receiving doxorubicin (mean 1.82), patients receiving cisplatin (mean 1.88) and patients receiving carboplatin (mean 1.45), Ps<0.01. 2) Mean nausea decreased steadily with age, P<0.0001. 3) Patients rating themselves more susceptible to nausea had significantly more nausea (adjusted mean = 2.51) than patients rating themselves less susceptible (adjusted mean = 1.92) and were 2.8 times more likely to experience severe nausea, Ps<0.0001. 4) Expected nausea was a significant predictor of average nausea, P=0.034, but not severe nausea, P=0.31. 5) No evidence that gender is a significant predictor of nausea in 299 patients with gender neutral cancers, P=0.35. CONCLUSIONS: Specific patient characteristics, especially younger age and perceived susceptibility to nausea, can help clinicians in the early identification of patients who are more susceptible to treatment-related nausea.